2016
DOI: 10.1177/0271678x15618977
|View full text |Cite
|
Sign up to set email alerts
|

Role of prostacyclin signaling in endothelial production of soluble amyloid precursor protein-α in cerebral microvessels

Abstract: We tested hypothesis that activation of the prostacyclin (PGI 2 ) receptor (IP receptor) signaling pathway in cerebral microvessels plays an important role in the metabolism of amyloid precursor protein (APP). In human brain microvascular endothelial cells activation of IP receptor with the stable analogue of PGI 2 , iloprost, stimulated expression of amyloid precursor protein and a disintegrin and metalloprotease 10 (ADAM10), resulting in an increased production of the neuroprotective and anticoagulant molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(47 citation statements)
references
References 78 publications
1
46
0
Order By: Relevance
“…The amyloidogenic processing pathway is unaffected by PGI 2 in brain microvessel endothelial cells (Table 1). Furthermore, deletion of PPAR␦ abolished the iloprost-induced ADAM10 activation and release of sAPP␣ in brain microvessel endothelial cells, thus demonstrating that PGI 2induced generation of sAPP␣ is also dependent on activation of PPAR␦ (78).…”
Section: Role Of Prostacyclinmentioning
confidence: 86%
See 2 more Smart Citations
“…The amyloidogenic processing pathway is unaffected by PGI 2 in brain microvessel endothelial cells (Table 1). Furthermore, deletion of PPAR␦ abolished the iloprost-induced ADAM10 activation and release of sAPP␣ in brain microvessel endothelial cells, thus demonstrating that PGI 2induced generation of sAPP␣ is also dependent on activation of PPAR␦ (78).…”
Section: Role Of Prostacyclinmentioning
confidence: 86%
“…Several isoforms of a disintegrin and metalloproteinase (ADAM) are responsible for ␣-secretase activity: ADAM9, ADAM10, and ADAM17. In human cerebrovascular endothelium, ADAM10 (but not ADAM9 or ADAM17) appears to be the most relevant constitutively active ␣-secretase, even though all three isoforms are expressed in endothelial cells (78,100).…”
Section: Soluble App␣mentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are supported by recent work on prostacyclin signaling influencing APP processing mechanisms. Agonist activation of the IP receptor was found to increase the expression of the amyloid precursor protein, resulting in the increased production of Aβ (49). Another report suggests that downstream activation of the PKA/CREB pathway after prostacyclin injections induces upregulation of γ-secretase cleaving enzymes and leads to an accumulation of Aβ c-terminal fragments in an APP/PS1 transgenic mouse model (50).…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have suggested that PGI2 may have some impact on neurodegenerative disorders such as Alzheimer's disease (47,48). He et al (49) was able to show that agonist-induced activation of the IP receptor-stimulated production of soluble APPα, a neuroprotective isoform of the amyloid precursor protein, in isolated human microvascular endothelial cells. Wang et al (50) demonstrated that injections of PGI2 into an amyloid precursor protein/presenilin 1 transgenic mouse model increased Aβ levels and proposed this was due to upregulation of the amyloid cleaving proteins, γ-secretase APH1α, and APH1β, via the PKA/CREB and JNK/c-Jun pathways.…”
Section: Introductionmentioning
confidence: 99%